CAFE LIFE VISUALIZATION IN DIGITAL ARTWORK - Sucita, I Komang; Sucipta, I Wayan Adi; Budiaprilliana, Luh (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This independent project report is entitled "Visualization of Cafe Life' in Digital Artwork and aims to reveal the phenomenon of life in a coffee shop through digital artwork. This study explores how the function of a coffee shop has shifted, which now not only provides coffee, but also sells a lifestyle that is popular with many people. This study also illustrates the anxiety that the author faces when carrying out his two daily activities as a barista and a student. The process of creating this digital artwork involves stages of exploration, improvisation, and formation, which are realized using digital media such as iPads and illustration software. The result is a series of digital illustration artworks that identify aspects of life in a coffee shop, and the researcher's personal challenges in carrying out two activities. There are six works produced, all of which are based on digital illustrations and the presentation media themselves vary from drinking cups, coffee grinders, tote bags, and t-shirts. This research contributes to the understanding of cafe life as a socio-cultural phenomenon and technological development, and offers a new perspective in creating digital artwork that is relevant to the development of the times. It is hoped that this work can inspire students, artists, and the younger generation to continue exploring and developing their creative potential through the use of digital technology and direct experience in everyday life.